Analysis and prediction of the conflict management styles of SPC school administrators - Javato, Marie Renee (Animo Repository, 1987)
This study is an analysis of conflict management styles of SPC school administrators all over the Philippines and the prediction of their choice of these styles in the light of certain variables. The study utilized the descriptive-analytical and correlational method of research. It aimed to determine conflict management styles of SPC school administrators all over the Philippines during the school year 1986-87 and the correlates of the construct under analysis. Information were elicited from the respondents mainly through questionnaires and records from the archives of the SPC Congregation in the Philippines. Three forms of questionnaires were used. Questionnaire A is a standardized questionnaire entitled Thomas-Kilmann Conflict Mode Instrument (TKCMI). Questionnaire Form B was constructed by the researcher to assess the appropriateness of respondent's conflict handling styles. Questions in Questionnaire Form C were lifted from some diagnostic questions in TKCMI utilized to determine possible reasons for the overuse and underuse of each of the five conflict handling styles--competing, collaborating, compromising, avoiding and accommodating, used as dependent variables in the study. Findings in the conflict management styles of Sister administrators indicated high use of avoiding style in all levels of management position. Their least used style was competing style which varied from low use for the middle and first line administrators and average use for the top level administrators. The youngest group of Sister administrators, aged 30-39 years, had the propensity to use the compromising style of conflict management.There was unanimity among all groups of administrators in their bias for avoiding style of conflict management, although they tended to use it inappropriately. All groups of administrators had average use of collaborating style and they used it very appropriately. Top level administrators had average use of competing style the others had low use for it. Generally, there was no significant differences in administrators' choices of the accommodating, avoiding, collaborating, and compromising styles of conflict management. An exception was the significant difference (p=.05) found in the use of competing style between administrators in Luzon and those in Visayas and Mindanao. There was a high significant correlation between geographical location where the Sisters were assigned and their use of conflict management styles. Administrators in Luzon used the competing style highly, while those in the Visayas and Mindanao were partial to compromising style. The best predictors for Sisters' use of the competing style of conflict management were geographical location and educational attainment for the collaborating style, geographical location and educational attainment for the compromising style, age, professional experience, and geographical location for the avoiding style, age and number of years as religious, and for the accommodating style, geographical location and age. Management position seemed not to have any influence over their choice of conflict management style. Finally, the religious orientation of the SPC administrators had a very great impact and influence on their conflict management styles.